2021
DOI: 10.22317/jcms.v7i6.1098
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of over-the-counter drug abuse among adults in Jeddah, Saudi Arabia

Osama Yousif Safdar,
Ghaidaa Faisal Albaz,
Sara Mohammed Mannan
et al.

Abstract: Objectives: Self-medication, also known as the use of over-the-counter drugs, can be defined as the economical choice of using treatments that have not been prescribed, recommended, or controlled by a certified healthcare professional, which can be found in pharmacies or convenience stores to treat self-recognized illnesses or symptoms. Previous studies on self-medication in Saudi Arabia are limited; thus, this study aimed to evaluate the prevalence of over-the-counter drug abuse among an adult population in J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Particularly, the ease of access to over-the-counter medications, especially through convenience stores, has increased the cases of abuse that result in hospitalizations [24][25][26]. Further, reports indicate an increase in the misuse of over-the-counter drugs, particularly among the elderly [27,28]. These tendencies have become especially evident in the past decade, and measures are necessary to control them.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, the ease of access to over-the-counter medications, especially through convenience stores, has increased the cases of abuse that result in hospitalizations [24][25][26]. Further, reports indicate an increase in the misuse of over-the-counter drugs, particularly among the elderly [27,28]. These tendencies have become especially evident in the past decade, and measures are necessary to control them.…”
Section: Discussionmentioning
confidence: 99%
“…Patients' understanding of their prescribed medications regarding their names, purpose, dosage schedule, potential side effects, and any special instructions associated with the medication is essential for lowering prescription mistakes, enhancing adherence, and raising patient satisfaction [4]. Research has demonstrated that insufficient health literacy leads to poor health outcomes, especially when it comes to misinterpreting prescription usage instructions [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…A recent Saudi study reported high prevalence of sedative misuse among university students ( Fadhel, 2022 ). A study conducted from a major city Saudi city (Jeddah) documented the prevalence of inappropriate and harmful OTC use among adults wherein they found that a high significant rate (exceeding 50%) of OTC medication use ( Safdar et al, 2021 ). Also, inappropriate use of medications was identified by another study in Saudi Arabia, where half of the study participants claimed that they knew someone who had misused medications ( Tobaiqy et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%